Pengaruh Manajemen Waktu, Motivasi Belajar, Dan Perilaku Prokrastinasi Terhadap Keberhasilan Akademik Mahasiswa: (Studi Kasus Pada Mahasiswa Kelas Karyawan Semester III dan V FEB Universitas PGRI Semarang Tahun Akademik 2020/2021 - Meta Ika Andrayani; Ratih Hesty Utami Puspitasari; Dian Apradika Kusumawati (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2022)
This study aims to analyze the effect of time management on student academic success, analyze learning motivation on student academic success, analyze procrastination behavior on student academic success, and analyze time management, learning motivation, and procrastination behavior on student academic success. The research unit is student employee class semester III and V FEB PGRI University of Semarang academic year 2020/2021. Data collection was carried out by distributing questionnaires via google form, with a total of 80 students as respondents. Methods of data analysis using multiple linear regression using SPSS software version 25. The results showed that time management on student academic success had a positive and significant effect. Learning motivation on student academic success shows a negative and insignificant effect. Procrastination behavior on student academic success shows a negative and insignificant effect. Then simultaneously time management, learning motivation, and procrastination behavior on student academic success have a positive and significant effect of 15.6%.)